Preparation of 5-fluorouracil loaded chitosan microtube via in situ precipitation for glaucoma drainage device application: in vitro and in vivo investigation. Issue 14 (4th October 2021) - Zhao, Xia; Liu, Sihao; Han, Yuemei; Wang, Yuqin; Lin, Quankui
Abstract: The main reason for the failure of glaucoma drainage devices is the chronic inflammatory reaction caused by the poor biocompatibility of biomaterials, which leads to the migration and proliferation of scleral fibroblasts surrounding the devices thus forming the encapsulation that will block the aqueous humor drainage channel. In order to inhibit the reaction of scleral fibroblasts after glaucoma drainage device implantation, this study designed and fabricated a 5-fluorouracil (5-FU) loaded chitosan microtube (CMT) for glaucoma aqueous humor drainage. The CMTs were made by template based adsorption-precipitation method using chitosan with excellent biocompatibility as raw material due to its characteristic of pH dependent solubility. The physical properties of CMTs were investigated. The in vitro and in vivo biocompatibilities were studied as well. The developed drainage device is expected to possess the dual function of reducing intraocular pressure and inhibiting excessive fibrosis after glaucoma drainage device implantation, thereby providing a novel way for the research of glaucoma drainage devices.